1999
DOI: 10.1093/ndt/14.12.2898
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase gene polymorphism in intron 4 affects the progression of renal failure in non-diabetic renal diseases

Abstract: Among the frequencies of ecNOS intron 4 gene polymorphism, a allele displayed a significantly higher frequency in cases with end-stage renal failure (ESRF) not caused by diabetic nephropathy. ecNOS gene polymorphism in intron 4 appears, therefore, to affect the progression of renal failure in non- diabetic renal diseases, but the same conclusion could not be drawn in diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
64
3
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 19 publications
5
64
3
1
Order By: Relevance
“…This is a common SNP associated with a variety of diseases such as hypertension, pre-eclampsia, placental abruption or myocardial infarction (35)(36)(37). On the other hand, eNOS rs2070744 is a C>T conversion within intron 4 and it also has been studied in ovarian cancer and renal diseases (22,38). The wide range of phenotypes displayed by these variations proves the involvement of nitric oxide in multiple pathways, including carcinogenesis and tumor progression (39).…”
Section: Discussionmentioning
confidence: 99%
“…This is a common SNP associated with a variety of diseases such as hypertension, pre-eclampsia, placental abruption or myocardial infarction (35)(36)(37). On the other hand, eNOS rs2070744 is a C>T conversion within intron 4 and it also has been studied in ovarian cancer and renal diseases (22,38). The wide range of phenotypes displayed by these variations proves the involvement of nitric oxide in multiple pathways, including carcinogenesis and tumor progression (39).…”
Section: Discussionmentioning
confidence: 99%
“…Asakimori et al, in 2001, found a significantly higher frequency of the ecNOS 4a allele in haemodialysis patients, both non-diabetic and diabetic, and therefore suggested that the polymorphism in intron 4 of the ecNOS gene may have influence on the progression of renal disease. Wang et al, in 1999, in their study of 302 subjects with endstage renal disease and 248 healthy controls found a significantly higher frequency of the ecNOS 4a allele in patients with ESRD caused by non-diabetic primary renal diseases. Freedman et al2000 evaluated the role of four NOS gene polymorphisms in ESRD patients and found that the a allele of the ecNOS 4 polymorphism in the NOS gene was associated with all-cause ESRD in probands and their siblings compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 91%
“…Regarding the other polymorphism (rs1799983), its effect is still controversial since the aspartate substitution at 298 does not seem to have a major effect in modulating eNOS activity in vivo [21], however an association of the T allele with pre-eclampsia [11] and ischemic heart disease [5] was reported strengthening the importance of this polymorphism. Studies with intron 4 VNTR polymorphism revealed an association between the 4a allele with coronary heart disease [16] and renal disease [4,23]. Another study found that eNOS intron 4 VNTR gene polymorphism is related to endothelial dysfunction and vasculopathy in sickle cell disease [19].…”
Section: Discussionmentioning
confidence: 99%